High Genetic Diversity and Insignificant Interspecific Differentiation in Opisthopappus Shih, an Endangered Cliff Genus Endemic to the Taihang Mountains of China - Rongmin Guo; Lihua Zhou; Hongbo Zhao; Fadi Chen (The Scientific World Journal)
Opisthopappus Shih is endemic to the Taihang Mountains, China. It grows in the crevice of cliffs and is in fragmented distribution. This genus consists of two species, namely, O. taihangensis (Ling) Shih and O. longilobus Shih, which are both endangered plants in China. This study adopted intersimple sequence repeat markers (ISSR) to analyze the genetic diversity and genetic structure from different levels (genus, species, and population) in this genus. A total of 253 loci were obtained from 27 primers, 230 of which were polymorphic loci with a proportion of polymorphic bands (PPB) of up to 90.91% at genus level. At species level, both O. taihangensis (PPB=90.12%, H=0.1842, and I=0.289) and O. longilobus (PPB=95.21%, H=0.2226, and I=0.3542) have high genetic diversity. Their respective genetic variation mostly existed within the population. And genetic variation in O. longilobus (84.95%) was higher than that in O. taihangensis (80.45%). A certain genetic differentiation among populations in O. taihangensis was found (Gst=0.2740, Φst=0.196) and genetic differentiation in O. longilobus was very small (Gst=0.1034, Φst=0.151). Gene flow in different degrees (Nm=1.325 and 4.336, resp.) and mating system can form the existing genetic structures of these two species. Furthermore, genetic differentiation coefficient (Gst=0.0453) between species and the clustering result based on the genetic distance showed that interspecific differentiation between O. taihangensis and O. longilobus was not significant and could occur lately.